Multichannel Management A Normative Model Towards Optimality - Gruber, Gottfried (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2018)
A company operating various sales channels, e.g. the Internet and a traditional shop, inevitably faces a tricky coordination problem. As prevalent approaches often do not lead to a satisfying solution, the author suggests a normative model to offer directions for the optimal channel coordination. The model is based on stochastic purchase and switching probabilities, given certain conditions like prices and supportive marketing activities (like delivery time or shop environment). A company can fit its consumer base to the model and simulate various effects on its earnings by altering prices or marketing activities. The model is a market-based playground to develop new holistic strategies for a multichannel company without affecting the market.